Kendali Ketahanan Genetik Padi terhadap Penyakit Tungro - Muliadi, Ahmad; Nasrullah, Nasrullah; Sumardiyono, Y. B.; Trisyono, Y. Andi (Jurnal Penelitian Pertanian Tanaman Pangan, 2014)
Genetic study of resistant to rice tungro disease was carried out in Indonesian Agricultural Biotechnology and Plant Genetic Resources Institute, Bogor. TN1 rice variety was used as susceptible parent and OBSTG02-124 line as resistant parent. Cross combinations between resistant vs susceptible parents obtained 6 crosses. The study materials consisted of 55 plants of susceptible parent (P1) and 35 plants of resistant parents (P2), 70 F1 plants, 70 F1R plants, 100 BC1-1 plants, 100-BC1-2 plants, and 300 F2 plants. The probable maternal effect was identified by comparing resistant to tungro disease of F1 plants vs. the F1 of their reciprocal crosses, using the t-test. Each population was planted in pot containing 5 kg of soil. Plants were inoculated at 7-10 days old with virus tungro isolate Subang, using 4-5 green leafhoppers for 5 hours. Visual symptoms were observed based on the Standard Evaluation System for Rice. ELISA test (non Precoated I-ELISA) was performed at 21 days after inoculation, using polyclonal antibodies RTSV (S) and the combined RTBV and RTSV (BS). The results showed that there was no maternal effect on the inheritance of tungro disease resistance. The resistant to tungro in OBSTG02-124 was controlled by two complementary recessive genes. The moderate heritability indicated that the environment play role in determining the degree of resistant to tungro desease.